(untitled) (Global Journal of Medical Research, 2018)
at Jimma municipal abattoir with the aim of identifying main pathological lesions causing organs and carcass condemnation, and associated direct financial losses. In this, 384 sheep were recruited to the study using systematic random sampling and standard antemortem (AM), and postmortem inspection (PMI) procedures were employed. Nasal discharge, tick infestation, coughing, lameness, emaciation, depression and salivation are recordedas the major AM findings of the current study. Accordingly, 47 (12.2%) sheep showed signs of diseases and abnormalities; of which 23 (6%) were conditionally approved whereas 11 (2.9%) sheep were unfit and judged to be detained and rejected. In the present study age, body conditions and geographic origin of the animals were considered as study variables, and the results showed BCS and age groups had statistically higher (p ≤ 0.05) rejection probabilities.